Securing Methyl-Tert-Butyl-Ether from Methanol and Butylene-Butadiene Fraction on Sulpho-Cationites and Zeolite-Bearing Catalyst; 39th International Petroleum Conference, Bratislava, Slovak Republic, September 20-23, 1999 : proceedings; Vol. 2 - Erofeev V. I. Vladimir Ivanovich (1999, 1999)
В фонде НТБ ТПУ отсутствует